Are we ready for long‐acting? A feasibility evaluation of long‐acting cabotegravir–rilpivirine in clinical practice. Issue 10 (9th June 2022) - Borghetti, Alberto; Farinacci, Damiano; Ciccullo, Arturo; Dusina, Alex; Moschese, Davide; Iannone, Valentina; D'Angelillo, Anna; Lombardi, Francesca; Donne, Valentina Delle; Massaroni, Valentina; Visconti, Elena; Tamburrini, Enrica; et al.
Abstract: Cabotegravir and rilpivirine are the first drugs to be approved as injectable therapy to treat individuals with HIV. Despite encouraging results, the guidelines specify strict criteria for eligibility that could limit the feasibility of this strategy. We collected the clinical data of HIV‐positive patients who were being treated at a single, third‐level center in Italy. All patients were on stable therapy and showed suppressed viral load on their most recent analyses. We performed a cross‐sectional analysis of the clinical and viro‐immunological characteristics of this population and excluded patients who had previous virological failures, resistance‐associated mutations (RAMs) to rilpivirine or integrase inhibitors in the historical genotype, hepatitis B infection, absence of previous genotypes, and the coexistence of HIV‐subtype A and obesity. Our aim was to evaluate the proportion of patients who could be eligible for switching to this strategy. one thousand seven hundred fifty‐two patients were eligible. One hundred and forty‐eight were excluded because of a detectable viral load. With regard to the exclusion criteria, 48 patients had coinfection with hepatitis B virus, and 744 had a history of previous virological failures. Of the 896 patients with at least one genotypic resistance test, 161 had one or more RAMs to rilpivirine and 3 had RAMs to cabotegravir. None of the patients presented the combination of obesity and the A viral subtype. Overall, 31.2% of the patients were ineligible for cabotegravir–rilpivirine, and the proportion increased to 47.3% when we considered only patients with all available information concerning resistance tests. Approximately half of our cohort of patients did not fulfill the criteria and even more patients were potentially ineligible for cabotegravir–rilpivirine due to the lack of genotypic resistance tests. Also, fertile women had to be excluded due to the lack of data about this combination during pregnancy and breastfeeding.